VILLAGE AREA MAP MAKING TRAINING IN LANCANG GARAM VILLAGE BASED ON THE GEOSPATIAL DATA USING AUTOCAD SOFTWARE - Effan Fahrizal; Soraya Masthura Hassan; Dela Andriani; Andrit Yamesa; Dafa M Nur (Universitas Muhammadiyah Aceh, 2022)
Currently, the development of technology has been very fast. In the digital era, many humans jobs have been replaced by the technology. One of the most widely used today is the use of the computer software in a variety humans work, ranging from simple levels of work to complex levels. Making regional maps for various purposes will be easier by using a computerized system. One of the widely used computer software to help map area is AutoCAD. The method used is the Tracing Method in AutoCAD using Geospatial data available on Google Earth. The target of this community service is the government of Lancang Garam Village. The aim is to introduce and train AutoCAD as a computer software that can be used in making the village map. The results obtained in this study were in the form of knowledge of community and the officials in Lancang Garam Village related on the use of AutoCAD Software, especially in map making. Keywords: Map Making, AutoCAD, Geospatial